Surface activity as basis for pharmaceutical applications of hydrocolloids: A review - Emmanuel O. Olorunsola, Musiliu O. Adedokun (Journal of Applied Pharmaceutical Science, 2014)
Hydrocolloids are polymeric substances with mild to moderate surface activity. They are widely used as excipients in drug delivery systems where they serve various purposes such as suspending, emulsifying, wetting, foaming, solubilizing, stabilizing and bioadhesive agents as well as permeation enhancers. The surface activity and pharmaceutical applications of some hydrocolloids were reviewed in this study. The review showed that most natural hydrocolloids are characterized by higher critical micelle concentrations (CMC) compared to semi-synthetic and synthetic ones. Cashew and khaya gums (exudates gums) with hydrophile – lipophile balance (HLB) values in the range of 15 - 18 possess solubilizing property. Dispersions of afzelia and prosopis gums (seed gums) have higher viscosity compared to acacia gum and may produce more stable disperse systems. Semi-synthetic and synthetic hydrocolloids like sodium carboxyl methylcellulose and polyvinylpyrrolidone are characterized by low CMC and exhibit very high surface elasticity at concentrations above CMC thus exhibiting high bioadhesive strength. Therefore, surface activity is the basis for most pharmaceutical applications of hydrocolloids and the application of individual hydrocolloid depends on its adsorption power, CMC, HLB value and bioadhesive strength.
Keywords: Hydrocolloids,pharmaceutical applications, surface activity.